DHTKD1 is essential for mitochondrial biogenesis and function maintenance. Issue 21 (27th September 2013) - Xu, Wangyang; Zhu, Houbao; Gu, Mingmin; Luo, Qingqiong; Ding, Jieying; Yao, Yuting; Chen, Fuxiang; Wang, Zhugang
Abstract : Maintaining the functional integrity of mitochondria is crucial for cell function, signal transduction and overall cell activities. Mitochondrial dysfunctions may alter energy metabolism and in many cases are associated with neurological diseases. Recent studies have reported that mutations in dehydrogenase E1 and transketolase domain‐containing 1 ( DHTKD1 ), a mitochondrial protein encoding gene, could cause neurological abnormalities. However, the function of DHTKD1 in mitochondria remains unknown. Here, we report a strong correlation of DHTKD1 expression level with ATP production, revealing the fact that DHTKD1 plays a critical role in energy production in mitochondria. Moreover, suppression of DHTKD1 leads to impaired mitochondrial biogenesis and increased reactive oxygen species (ROS), thus leading to retarded cell growth and increased cell apoptosis. These findings demonstrate that DHTKD1 contributes to mitochondrial biogenesis and function maintenance. Abstract : DHTKD1 deficiency leads to mitochondrial dysfunction. DHTKD1 deficiency impairs mitochondrial biogenesis. DHTKD1 deficiency leads to ROS accumulation. DHTKD1 is involved in cell proliferation and apoptosis.